Biocompatible and Bioactive Peg-Based Resin Development for Additive Manufacturing of Hierarchical Porous Bone Scaffolds - Utrera-Soto, A (Elsevier Ltd, 2023)
Bone diseases can often result in patient bone fragility. Different bone problems include low bone density, osteoporosis, and other bone diseases. Such bone diseases, ailments, and malfunctions often require complex and expensive treatments. In this study, we synthesized a new type of DLP resin for 3D printing purposes based on poly(ethylene glycol diacrylate) (PEGDA) and acrylic acid (AAc). In addition, using a porogen within the photopolymerizable resin allowed us to fabricate hierarchical interconnected porous structures. These structures combine the pores resulting from the CAD design with those obtained by the lixiviation of the porogen. Finally, bioactive particles were added to the mixture to increase the material s biocompatibility, thus proving the strategy s potential to include active compounds for particular purposes. Our results demonstrate that including the photoabsorber, Orange G, considerably increases the printing precision and resolution of the synthesized resin, making it possible to obtain printed parts with intricate and complex geometries with high accuracy and definition. Nano-hydroxyapatite (nHA) inclusion significantly increases the material s biocompatibility and mechanical stiffness (∼47 % increase, from 5.47 MPa to 8.02 MPa). © 2023